PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING - Handriyani, Arik Novia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to examine and analyze the influence of Corporate Social Responsibility (CSR) to the company value with profitability as the moderating variable. Manufacturing companies whichare listed in the Indonesia Stock Exchange for 3 years period of observation (2009-2011) are used assamples in this research. Data is collected by using sampling purposive methods and the hypothesistest is performed by using Moderated Regression Analysis (MRA). The result of this researchindicates that the disclosure of CSR has significant influence to the company value and profitability asthe moderating variable cannot influence the relation CSR disclosure to the company value. Keywords:Â  Corporate Social Responsibility (CSR), firm value, profitability